DIGITAL CONNECTIVITY AND ACCESS TO ONLINE RESOURCES AS PREDICTORS OF GLOBAL COMPETENCE AMONG PRE-SERVICE TEACHERS IN A GLOBALISED WORLD IN OYO STATE - Ajayi, Olatunde O.; Adediran, Yinka Oluranti; Oriola, Mufutau Oluwakemi (African Journal of Social and Behavioural Sciences, 2025)
This study explores the predictive roles of digital connectivity and access to online resources in shaping global competence among pre-service teachers in Colleges of Education in Oyo State. A correlational survey research design was employed, involving 310 pre-service teachers selected through simple random sampling from two institutions. Data were collected using three self-designed instruments: the Pre-service Teachers’ Digital Connectivity Scale (PTDCS), the Pre-service Teachers’ Access to Online Resources Scale (PTAORS), and the Pre-service Teachers’ Global Competence Scale (PTGCS). Statistical analyses, including Descriptive Statistics, Pearson Product-Moment Correlation, and Multiple Regression, revealed that while preservice teachers possess moderate levels of digital connectivity and access to online resources, barriers such as unreliable internet and limited institutional support hinder their potential. Nonetheless, they demonstrated moderate to high levels of global competence, particularly in applying global knowledge and engaging with global issues. The study concludes that enhancing digital infrastructure and improving access to online academic resources can significantly boost the global competence of pre-service teachers, providing essential insights for educational policy and curriculum development better to prepare teachers for an interconnected and diverse world.